Effect of Mechanochemical Reaction on Palygorskite in Adsorption Properties - Zhao, Difang; Li, Minghua; Xie, Jinsong (Asian Journal of Chemistry, 2014)
Using high-energy facility, the purified palygorskite was activated by mechanochemical treatment and preparing the urtral activated absorbent particle by the method of ball milling. With the aids of themogravimetric analysis and transmission electron microscope, the changes of thermal stability, particle size and microstructure were analyzed. The results show that the adsorption properties of mechanochemical reaction palygorskite were increased greatly, the particles were flat and minimized and the adsorbent particles has the good dispersbility.